EMPATI TERHADAP SISWA BERKEBUTUHAN KHUSUS: DITINJAU DARI JENJANG PENDIDIKAN INKLUSI DAN JENIS KELAMIN - Faizah, Faizah; Kurniawati, Yunita; Rahma, Ulifa (Jurnal Psikologi, 2017)
Empathy is a part of important things to support students with special needs for their interpersonal development. Moreover, it is also a prominent factor of student’s mental health in inclusive school. This research aimed to investigate student’s empathy based on their educational level. The methods of this research was quantitative.,the instruments used were Empathy Scale from Index of Empathy for Children and Adolescents. Anova and t-test were used to analyze data. The results showed that there were differences empathy based on educational level (F = 435.541 p < .001). Empathy on Junior High School was higher than of other educational levels. Empathy on Junior High School (M = 38.5; SD = 6.135 ), University (M = 29.27; SD = 3.927), Senior High School (M = 20.89; SD = 3.406), Elementary School (M = 14.40; SD = 6.509 ). The results showed that there were differences empathy based on sex (t = 3.940 p< .001). The results showed that empathy on female students (M = 27.33 SD = 9.740) higher than male students (M = 23.75 SD = 9.581).